MLA handbook (The Modern Language Association of America, 2021)
"The ninth edition of the MLA Handbook is a textbook and reference guide that offers student writers and writing instructors guidance on creating works-cited-list entries in MLA style using the template of core elements. It features advice on punctuation, grammar, inclusive language, formatting research papers, and in-text citations. Includes an appendix of sample works-cited-list entries, illustrations, and an index"--